2010
DOI: 10.1371/journal.pone.0010472
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interactions Show the Importance of rRNA Modification Machinery for the Role of Rps15p during Ribosome Biogenesis in S. cerevisiæ

Abstract: Rps15p, an essential ribosomal protein, was previously shown to be critical for nuclear export of small subunit pre-particles. We have designed a synthetic lethal screen in Saccharomyces cerevisiæ to identify its genetic partners and further elucidate its role during ribosomal biogenesis. Our screen revealed interactions with mutants affected at various stages during ribosome biogenesis, from early nucleolar steps to nuclear export. Mutations were identified in genes encoding proteins involved in early ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(48 reference statements)
3
5
0
Order By: Relevance
“…Rps15 was shown to genetically interact with Slx9 and the pre40S associated factor Bud23 [56]. Here we found that rps15-1 , a previously reported impaired allele of Rps15 [56], when combined with the mex67 Δ C1 allele is synthetically lethal (Figure 8A). However, growth of rps15-1 mutant remained unaffected when combined with the mex67 Δ loop and the mtr2 Δ loop116-137 alleles (Figure 8A and Figure 8B).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Rps15 was shown to genetically interact with Slx9 and the pre40S associated factor Bud23 [56]. Here we found that rps15-1 , a previously reported impaired allele of Rps15 [56], when combined with the mex67 Δ C1 allele is synthetically lethal (Figure 8A). However, growth of rps15-1 mutant remained unaffected when combined with the mex67 Δ loop and the mtr2 Δ loop116-137 alleles (Figure 8A and Figure 8B).…”
Section: Resultssupporting
confidence: 65%
“…The ribosomal protein Rps15 has been implicated in pre40S subunit export, although its precise contribution to export step remains unclear [54], [55]. Rps15 was shown to genetically interact with Slx9 and the pre40S associated factor Bud23 [56]. Here we found that rps15-1 , a previously reported impaired allele of Rps15 [56], when combined with the mex67 Δ C1 allele is synthetically lethal (Figure 8A).…”
Section: Resultssupporting
confidence: 51%
“…While there has been much progress in the past decade in characterizing rRNA processing and ribosome biogenesis, the intricacies of these processes continue to hamper identification and/or the assignment of precise roles for several of the participating factors (Lafontaine and Tollervey, 2001 ; Fromont-Racine et al, 2003 ; Deutscher, 2009 ; Mullineux and Lafontaine, 2012 ). Efforts to identify proteins contributing to rRNA maturation pathways have recently turned to large-scale genetic and computational screens (Li et al, 2009 ; Bellemer et al, 2010 ). Two proteins identified in such a screen in the yeast Saccharomyces cerevisiae , TSR3 and TSR4, were specifically linked to the processing of the 20S rRNA intermediate transcript which gives rise to the mature 18S transcript (Li et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an earlier, nucleolar function of Rps15 was revealed by a synthetic lethality study with a thermosensitive rps15-1 mutant, uncovering genetic links of RPS15 with NHP2, UTP15, SLX9 , and BUD23 . Combined mutations of NHP2, UTP15 or SLX9 with rps15-1 led to nucleolar accumulation of pre-40S particles and early pre-rRNA processing defects [ 36 ]. In contrast, the rps15-1 Δbud23 double mutant primarily showed nucleoplasmic pre-40S accumulation, and, therefore, defects in nuclear export of pre-40S particles [ 36 ].…”
Section: Introductionmentioning
confidence: 99%